ปัจจัยที่พึงพิจารณาในการเก็บรักษาและขนส่งสารเคมีอันตราย - ศรีสมพร หงษ์สุมาลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Nowadays, the growth of industrial production drives the demand of dangerous chemicals which are main raw materials in production increasing so fast. In order to save all from the danger, this research intends to study the factors need to be considered in the storage and transport of dangerous chemicals. The research s population is from manufacturers, import and distributors, warehousing and transportation company of dangerous chemicals located in Bangkok Metropolitan and perimeter only. The result of this study is concluded into 2 parts. Firstly, the factors to be considered in the storage and transport of dangerous chemicals. For the factors to be considered in the storage can be ranked orderly from the most importance from man, place, package, disposition, preventive plan, hazard communication, emergency plan, equipments and finally is technology and information system. For the factors to be considered in the transport can be ranked orderly from the most importance from man, truck and equipments, package, disposition, hazard communication, preventive plan, emergency plan and finally is technology and information system. Secondly, the present problems found in the storage and transport of dangerous chemicals. The study finds the top 3 problems in the storage are man, technology and information system and final two equal problems are equipments and place. For the top 3 problems in the transport are man, truck and equipments and finally is package